Measuring Cot-Side the Effects of Parenteral Nutrition on Preterm Cortical Function - Marchi, Viviana; Stevenson, Nathan; Koolen, Ninah; Mazziotti, Raffaele; Moscuzza, Francesca; Salvadori, Stefano; Pieri, Rossella; Ghirri, Paolo; Guzzetta, Andrea; Vanhatalo, Sampsa (Frontiers in Human Neuroscience, 2020)
Early nutritional compromise after preterm birth is shown to affect long-term neurodevelopment, however there has been a lack of early functional measures of nutritional effects. Recent progress in computational EEG analysis has provided means to measure the early maturation of cortical activity. Our study aimed to explore whether computational metrics of early sequential EEG recordings could reflect early nutritional care measured by energy and macronutrient intake in the first week of life. A higher energy or macronutrient intake was assumed to associate with improved development of cortical activity. We analysed multichannel EEG recorded at 32 weeks (32.4 +/-0.7) and 36 weeks (36,6 +/- 0.9) of postmenstrual age in a cohort of 28 preterm infants born before 32 weeks of postmenstrual age (range: 24.3-32 weeks). We computed several quantitative EEG measures from epochs of quiet sleep: i) spectral power, ii) continuity, iii) interhemispheric synchrony, as well as iv) the recently developed estimate of maturational age. Parenteral nutritional intake from day 1 to day 7 were monitored and clinical factors collected. Lower calories and carbohydrates were found to correlate with a higher reduction of spectral amplitude in the delta band. Lower protein amount associated with higher discontinuity. Both higher proteins and lipids intake correlated with more developmental increase in interhemispheric synchrony as well as with a better progress in the estimate of EEG maturational age. Our study shows that early nutritional balance after preterm birth may influence subsequent maturation of brain activity in a way that can be observed with several intuitively reasoned and transparent computational EEG metrics. Such measures could become early functional biomarkers that hold promise for benchmarking in future development of therapeutic interventions.